Intensity of physical activity and life satisfaction of physical education teachers - Zusková, Klaudia; Petričková, Lucia; Ortenburger, Dorota (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The profession of physical education (PE) teacher is an irreplaceable and a specific role. Involvement in physical activities (PA) during both working and non-working times is considered one of the most significant specificity of this profession. PE teachers can perform the activity of sports experts, e.g. referee, instructor or engage in sports as a leisure time activity in non-working time, which mingles with the profession of a teacher. All of this can be a manifestation of a unilateral load that can have an impact on life satisfaction (LS). Aim of Study. The aim of this article is to contribute to the LS findings among middle-aged PE teachers when reflecting the load intensity of PA expressed in MET-min/week in the teacher’s total time fund. Material and Methods. We obtained the crosssectional research data on the sample of 151 PE teachers –comprised of 82 women and 69 men – from primary and secondary schools in the Slovak Republic. The questionnaire methods used were: non-standardized questionnaire (basic socio-demographic data and professional characteristics); short version of the International Physical Activity Questionnaire – IPAQ; and 5-item The Satisfaction with Life Scale [11]. Results. The average value of total activity level was 3235 for women and 3772 MET-min/week for men. A significant difference in intense PA and overall PA score between men and women in favor of men has been demonstrated. The average gross score values of 23.39 for women and 22.96 for men were in the average LS range. A significant difference between men and women has not been demonstrated. No significant relationship between overall PA and LS has been confirmed. Conclusions. Considering the ambiguous results of the research investigating PA and LS relationships, we recommend further analysis of this relationship. Attention should also be paid to burn out prevention among people whose profession interferes with their non-work activities.
Keywords: IPAQ; MET; middle adulthood; SWLS